E-064 Remote non-flow related intracranial aneurysms (IAs) associated with dural arteriovenous shunts (DAVSs) – incidence, clinical presentation, treatment and outcome. a case series and review of the literature. (22nd July 2019) - Htun, W; Wang, W; Howk, M; David, C; Choi, I; Wakhloo, A
Abstract : Background: Intracranial aneurysms (IAs) associated with dural arteriovenous shunts (DAVSs) are rare and infrequently discussed in conjunction with brain arteriovenous malformation (bAVM). We studied at two cerebrovascular centers IAs and associated DAVSs. Patients and methods: Between 2005 and 2018, 103 subjects with DAVSs were retrospectively analyzed for the presence of remote IAs. Demographics, clinical symptoms, aneurysm and DAVS location, treatment and clinical outcomes were studied. Pertinent literature on IAs associated with DAVSs was also reviewed. Results: In our study the incidence of remote IAs associated with DAVSs was 13.6%. Fourteen patients with Borden type DAVS I-III (m/f 1:1; age: 32–84 yrs; mean: 60 yrs) harbored a total of 18 aneurysms. Five patients had multiple aneurysms. High cervical DAVSs were found in 4 subjects. Eleven patients presented with history of a high blood pressure. Most common symptoms were headaches and tinnitus (n= 6) followed by subarachnoid hemorrhage (SAH) and or intracranial hemorrhage (ICH) in 6 patients and cranial nerve deficit in one patient. Treatment was commenced in a staged fashion initially addressing the symptomatic lesion. Eleven DAVSs and 9 aneurysms were successfully treated endovascularly while one patient underwent surgery for his DAVS and 2 aneurysms were clipped. A total of 6 tiny unruptured aneurysms and one high-cervical DAVS as well as a frontal slow-flow DAVS did not receive any treatment for various reasons. Seven aneurysms were treated with and without stent-assisted coil embolization and one pericallosal artery aneurysm was successfully treated with a flow diverter. There were no treatment related complications. Follow-up angiography showed an untreated low-flow DAVS shrank in size and another DAVS spontaneously resolved. During clinical follow-up period, 11 subjects presented with a mRS score of 0 while 3 subjects had a mRS of 1. Literature review included a total of 28 cases with 41 aneurysms. Data were compared with our own findings. Conclusions: Since remote IAs were not flow-related but showed typical distribution, DAVSs may share the pathomechanism with IAs. Most IAs were located in the anterior circulation and half of the DAVS were found in the anterior cranial fossa. Aneurysm rupture was more common than a bleed from the DAVS, especially when multiple IAs were present. Carefully planned and executed EVT and surgery was effective for this complex population with an excellent long-term clinical outcome. Disclosures: W. Htun: None. W. Wang: None. M. Howk: None. C. David: None. I. Choi: None. A. Wakhloo: None.